Alle gemeinsam - Vielfalt spielerisch erkennen! - Gabriel, Lena (Grundschule Sport)

Review Writing as Part of the Doctoral Qualification Process in Theses-By-Publication. Results of an Interview Study With Ph.D. Students in German Sports Science - Jaitner, David; Gabriel, Lena; Zander, Benjamin

Des arbitrages éthiques face aux injonctions à la pratique physique dans les programmes de promotion de la santé : le cas des familles populaires en Europe - Grimminger-Seidensticker, Elke; Vieille Marchiset, G.; Knobé, S.; Aceti, M. (SociologieS.)

Zur Einführung in Kapitel 10 und 11 - Grimminger-Seidensticker, Elke; Brandl-Bredenbeck, Hans Peter; Gerlach, Erin; Krieger, Claus (Sportpädagogik. Eine Grundlegend)

Forschungsmethodische Zugänge - Grimminger-Seidensticker, Elke; Krieger, Claus (Sportpädagogik. Eine Grundlegung)

Herausforderungen der Sportpädagogik - Balz, Eckart; Gabriel, Lena; Wibowo, Jonas (Sportpädagogik)

Empirische Einsichten in das Review-Schreiben von Nachwuchswissenschaftler/innen - Gabriel, Lena; Jaitner, David; Zander, Benjamin (Ze-phir)

Immersive augmented reality system for the training of pattern classification with a myoelectric prosthesis - Boschmann, A; Neuhaus, Dorothee; Vogt, S; Kaltschmidt, C; Platzner, M; Dosen, S (Journal of neuroengineering and rehabilitation)

Health concepts among socially disadvantaged children in France, Germany and Switzerland - Grimminger-Seidensticker, Elke; Aceti, Monica; Knobé, Sandrine; Vieille Marchiset, Gilles (Health Promotion International)
Summary As health concepts develop through exposure to, and experience with particular contexts, and as health concepts influence health behaviour, it is important for actors in health promotion programmes to understand an individual’s health concepts. This study focussed on health concepts among socially disadvantaged children in France, Germany, Italy and Switzerland—a hitherto less researched population group. We conducted focus groups with a total of 167 children aged 7–11 years (mean=8.76 years, SD=0.68). The aim of this study was to explore if the life situation across four different countries leads to similar health concepts, and how the particular, national health discourses are reflected in the children’s health concepts. The data were analysed through a structured qualitative content analysis and revealed four categories: ‘Symbols/symptoms of health/illness’, ‘Emotionality’, ‘Healthy/unhealthy practices’, and ‘Consequences of health problems’. The children’s health concepts are linked to concrete events and objects, and they are able to think in logical sequences. However, the children’s causal argumentation is uni-dimensional; they do not cover the complexity of the development of health problems. In particular, overweight stands for illness and is exclusively the result of unhealthy practices. In their concepts, the children reflect the national health promotion programme discourses about overweight. They seem to understand the messages of health education as ‘behaving well means being healthy’; however, such a health education message initiates accusations of ‘unhealthy persons’. In consequence, challenges for sensitive health education programmes (at school) are discussed.

A 14-Week Intervention Study on Changing Preservice Teachers’ Psychological Perspectives on Inclusion: Explicit and Implicit Attitudes, Self-Efficacy, and Stress Perception Toward Inclusion - Lautenbach, Franziska; Korte, Johanna; Möhwald, Aiko; Heyder, Anke; Grimminger-Seidensticker, Elke (Frontiers in Education)

A 14-weeks intervention study on changing preservice teachers’ psychological perspectives related to teaching inclusively: Explicit and implicit attitude, self-efficacy, and stress perception towards inclusion - Grimminger-Seidensticker, Elke; Lautenbach, F.; Heyder, A.; Korte, J.; Möhwald, Aiko Julia (Frontiers in Education)

SUBCLINICAL DISORDERED EATING AND BODY DISSATISFACTION IN NORMAL WEIGHT CHILDREN—THE ROLE OF PHYSICAL ACTIVITY AND MOTIVES TO EXERCISE - Grimminger-Seidensticker, Elke; Korte, Johanna; Möhwald, Aiko; Trojan, Jörg (Journal of Physical Education & Health)

Quantitative and qualitative results of a body image pilot intervention in (pre)adolescent girls - Grimminger-Seidensticker, Elke; Korte, J. (Journal of Physical Education & Health)

Die Bedeutung unterschiedlicher Heterogenitätsmerkmale für das Erleben von Zustandsangst vor dem Sportunterricht in der Grundschule - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia; Korte, J. (Grundschulsport. Empirische Einblicke und pädagogische Empfehlungen)

Sportdidaktik - Grimminger-Seidensticker, Elke; Oesterhelt, V.; Gerlach, E.; Friedrich, G. (Lernen im Fach und über das Fach hinaus)

Körperbild, Bewegung und Sport in der Wahrnehmung von Grundschulkindern. Ergebnisse einer explorativen lnterviewstudie - Grimminger-Seidensticker, Elke; Korte, J.; Möhwald, Aiko Julia (sportunterricht)

Machthandlungen von Schüler*innen im Sportunterricht – Welche Rolle spielt das Sportlehrer*innenhandeln? - Grimminger-Seidensticker, Elke (sportunterricht)

Enhancing social cohesion in PE classes within an intercultural learning program: results of a quasi-experimental intervention study - Grimminger-Seidensticker, Elke; Möhwald, Aiko Julia (Physical Education and Sport Pedagogy)

Von Interkultureller Kompetenz und sportpädagogischem Können in postmigrantischen Gesellschaften. Grundlagen und Weiterentwicklung eines Forschungsprogramms - Grimminger-Seidensticker, Elke; Gieß-Stüber, P.; Möhwald, Aiko Julia (Sport im Kontext globaler Zusammenarbeit)

Zum Umgang mit Heterogenität im Sportunterricht - Grimminger-Seidensticker, Elke; Frohn, J. (Empirie des Schulsports)